2015
DOI: 10.1111/1753-6405.12325
|View full text |Cite
|
Sign up to set email alerts
|

Differences in grass pollen allergen exposure across Australia

Abstract: Objective Allergic rhinitis and allergic asthma are important chronic diseases posing serious public health issues in Australia with associated medical, economic, and societal burdens. Pollen are significant sources of clinically relevant outdoor aeroallergens, recognised as both a major trigger for, and cause of, allergic respiratory diseases. This study aimed to provide a national, and indeed international, perspective on the state of Australian pollen data using a large representative sample. Methods Atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 39 publications
0
46
0
Order By: Relevance
“…The “unclassified” group included pollen that were not identified into any of the categories specified above. Earlier studies in Sydney have shown two distinct grass pollen peaks: the first smaller peak occurs between January and April and the second major pollen peak between July to October but we do acknowledge that other species maybe present in the atmosphere throughout the year.…”
Section: Methodsmentioning
confidence: 53%
“…The “unclassified” group included pollen that were not identified into any of the categories specified above. Earlier studies in Sydney have shown two distinct grass pollen peaks: the first smaller peak occurs between January and April and the second major pollen peak between July to October but we do acknowledge that other species maybe present in the atmosphere throughout the year.…”
Section: Methodsmentioning
confidence: 53%
“…We have also observed that the timing of the grass pollen season differs between geographic locations and over time (Beggs et al 2015). Here, we investigate the drivers of variation in the characteristics of the grass pollen season across latitudinal and climatic gradients.…”
Section: Introductionmentioning
confidence: 93%
“…With the exception of the Palmerston North study of pine pollen, none of these papers focused on tree pollen. Recently, a series of publications have reviewed the available information about allergenic pollen levels in Australia and New Zealand and highlighted the emphasis placed to date on grass pollen [12][13][14][15]. As such, little is known about the levels of tree pollen in New Zealand, nor the extent to which such pollens could be contributing to the burden of allergenic rhinitis in New Zealand.…”
Section: Previous Monitoring Of Airborne Pollen In New Zealandmentioning
confidence: 99%